The Communication by Means of the Optical Fiber (International Journal of Innovative Research in Computer Science & Technology, 2021)
A fiber optics is a transparent, flexible  fabric made of plastic or glass with a diameter slightly  bigger than human hair. It's mostly used to transmit light  from one fiber end to the other. This kind of transmission  is often used in fiber optic communication, where an  optic fiber link delivers data over a longer distance and  with a higher bandwidth than an electrical line. The  optical fiber communication system and network is now  undergoing a significant transformation from a static,  scalable, energy-efficient, and flexible design to a  dynamic, scalable, energy-efficient, and adaptable  approach. We look at the evolution of optical network  technologies and methods in the fifth century in this  article. The fibre optics biosensor is extremely important  in the production of biosensors since it helps to quickly  miniaturise and integrate those targets. Fiber optics has  advanced dramatically since the fourth generation, with  data rates reaching 40-60 tbps, repeater spacing reaching  35000 km, and wavelengths reaching 1.5 micrometres.
Keywords: Time Division Multiplexing; Wavelength Division Multiplexing (WDM); Non-Return to Zero(NRZ); Fifth-Generation(5G); Elastic Optical Network(EON); Hybrid Optical Switching(HOS)